A Comparative Analysis of the Status of Homosexual Men in Indonesia and the Philippines - Ellisiah Uy Jocson; Wisnu Adihartono (Jember University Press, 2020)
Gender related discrimination has increased pervasively, especially as the fight for equality and acceptance takes center stage in the past few years. Women persistently demand the right to stand equally with men, and likewise, the Lesbian, Gay, Bi-Sexual, Transgender, Queer and Intersex Community (LGBTQI) seek the same equity. However, responses to gender and sexuality issues vary greatly across the world. The LGBTQI population is also difficult to determine given the intolerance of some Countries towards this community. On the topic of homosexuality, attitudes and presumptions prevail and act as barriers in acceptance of the ‘gay’ community. These obstacles hail from a multitude of concerns, spanning the areas of culture, religion and ethnicity, amongst others. This study seeks to analyze and determine the treatment of homosexual men in two multicultural countries: Indonesia and the Philippines. Repeated reports of gay suppression in Indonesia are a stark contrast to the seemingly high tolerance that gay people enjoy in the Philippines. This paper outlines the causes of these opposing treatments for gay communities in Indonesia and the Philippines.